Differences in Respiratory Muscle Responses to Hyperpnea or Loaded Breathing in COPD - Antenor Rodrigues (2020)
© Lippincott Williams & Wilkins. Introduction We aimed to compare acute mechanical and metabolic responses of the diaphragm and rib cage inspiratory muscles during two different types of respiratory loading in patients with chronic obstructive pulmonary disease. Methods In 16 patients (age, 65 ± 13 yr; 56% male; forced expiratory volume in the first second, 60 ± 6%pred; maximum inspiratory pressure, 82 ± 5%pred), assessments of respiratory muscle EMG, esophageal pressure (Pes) and gastric pressures, breathing pattern, and noninvasive assessments of systemic (V˙O2, cardiac output, oxygen delivery and extraction) and respiratory muscle hemodynamic and oxygenation responses (blood flow index, oxygen delivery index, deoxyhemoglobin concentration, and tissues oxygen saturation [StiO2]), were performed during hyperpnea and loaded breathing. Results During hyperpnea, breathing frequency, minute ventilation, esophageal and diaphragm pressure-time product per minute, cardiac output, and V˙O2 were higher than during loaded breathing (P < 0.05). Average inspiratory Pes and transdiaphragmatic pressure per breath, scalene (SCA), sternocleidomastoid, and intercostal muscle activation were higher during loading breathing compared with hyperpnea (P < 0.05). Higher transdiaphragmatic pressure during loaded breathing compared with hyperpnea was mostly due to higher inspiratory Pes (P < 0.05). Diaphragm activation, inspiratory and expiratory gastric pressures, and rectus abdominis muscle activation did not differ between the two conditions (P > 0.05). SCA-blood flow index and oxygen delivery index were lower, and SCA-deoxyhemoglobin concentration was higher during loaded breathing compared with hyperpnea. Furthermore, SCA and intercostal muscle StiO2 were lower during loaded breathing compared with hyperpnea (P < 0.05). Conclusion Greater inspiratory muscle effort during loaded breathing evoked larger rib cage and neck muscle activation compared with hyperpnea. In addition, lower SCA and intercostal muscle StiO2 during loaded breathing compared with hyperpnea indicates a mismatch between inspiratory muscle oxygen delivery and utilization induced by the former condition.